Ensure the generation and processing of inventory transactions through a web application for ground freight transportation equipment (2023)
As its general objective, the present investigation had to ensure the generation and processing of inventory transactions, along with the operating procedures that will enable its processing. The software was developed in the form of a responsive web application. The organization didn't have an operational model of systematized inventory transactions, and this is what is proposed in this investigation. The methodology for the development of the software product is the "Boehm's Spiral" model since it fits perfectly with the context of the project. For this project four cycles were identified:1) User administration module. 2) Request generation module: Requests Related to a work order. Requests not related to a work order. Request without consumption voucher. 3) View entered request. 4) Processing Module requests: Requests related to a work order. Requests not related to a work order. Request without consumption voucher. The final purpose was the development of a responsive application to facilitate the processing of inventory transactions.